Dew point temperature as overwetting indicator of enclosing structures - Kupriyanov Valery (E3S Web of Conferences, 2021)
Overwetting of enclosing structures is a negative factor of their operation. Due to the fact that it reduces thermal protection, it causes the corrosion processes and leads to enclosing structures materials destruction on account of alternating freezing and thawing. Present investigations on the analysis of condensation of moisture vapor and moist condition of enclosing structures does not allow for definition of overwetting rate of enclosures in the preset climate. These questions are also not regulated in the current normative documents. Enclosing structures developed as a result of conservation of energy have unpredictable accumulation of condensation and overwetting rate under service conditions. The article examines a new concept «dew point temperature» that is a characteristic of construction solution of enclosing structures and used materials. The dew point temperature is numerically equal to external temperature at which we can observe condensation in-plane of maximum overwetting of enclosing structures for the first time. It was demonstrated that every construction solution of enclosure has its own dew point temperature, according to which the amount of condensation in identical climatic conditions will be formed. The result of investigation is the assumption about the introduction of a new characteristic called «dew point temperature of enclosing structure» into the scientific discourse and into the check-list of mandatory thermotechnical values of enclosing structures. The dew point temperature describes the capacity of construction solution of enclosure for overwetting in the preset climatic conditions.